2013
DOI: 10.1364/oe.21.013305
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming temporal polarization instabilities from the latent birefringence in all-normal dispersion, wave-breaking-extended nonlinear fiber supercontinuum generation

Abstract: Abstract:The intrinsic weak birefringence in all-normal dispersion highly nonlinear fiber, particularly ultra-high-numerical-aperture fiber, generates supercontinuum with long term polarization instabilities, even for seed pulses launched along the perceived slow axis of the fiber. Highly co/anti-correlated fluctuations in energy between regions of power spectral density mask the extent of the spectral noise in total integrated power measurements. The instability exhibits a seed pulse power threshold above whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…through polarization modulation instability [30,31], which severely limits the applicability of ANDi SC sources in the ultrafast photonics applications mentioned above. However, this polarization-related noise can be effectively suppressed by increasing the birefringence of the fiber, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…through polarization modulation instability [30,31], which severely limits the applicability of ANDi SC sources in the ultrafast photonics applications mentioned above. However, this polarization-related noise can be effectively suppressed by increasing the birefringence of the fiber, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, above a certain threshold of output power, this SC suffers a hardly controllable nonlinear depolarization effect [1214], so that the spectrum of the SC defies the scalar generalized nonlinear Schrödinger equation (GNLSE) [13] and the polarization of the SC endures long-term instability [14]. In these prior works, the depolarization effect has been attributed to vector modulation instability [3,15].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we directly observe the short-term noise by polarized RIN measurements and the spectral decoherence through pulse compressibility assessment. Thus, the nonlinear depolarization and vector modulation instability not only negatively affect the controllability and long-term stability of the ANDi fiber SC generation [13,14], but also fundamentally limit the application of this technology when full spectral coherence or low-noise polarized source is required. By fabricating a dispersion-flattened ANDi photonic crystal fiber with a large intentional birefringence (>10 4 ), we suppress these effects and therefore develop a high-power broadband coherent SC laser.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has revealed that normal dispersion spectral broadening can lead to stable supercontinuum (SC) generation, provided that polarization modulation instability [9] is mitigated through propagation in polarization maintaining (PM) fibers [10]. While the broadening in the amplifier is not as extensive as SC generation in nonlinear optical fiber, the nonlinear phase shifts are still quite large at ϕ nl ∼ 5 − 12π [11].…”
mentioning
confidence: 99%
“…The output chirp of an ANDi laser operating with modest average power (∼500 mW, 22 nm bandwidth, and 130 fs FWHM transform limited pulse duration) contains a significant amount of TOD. In combination with small fluctuations in the power spectral density from the ANDi oscillator (<2%), the temporal structure from the uncorrected TOD on the pulse can drive large spectral fluctuations in all normal dispersion SC generation [10]. Eliminating the influence of spectral fluctuations from the ANDi oscillator during nonlinear broadening in the amplifier is critical; requiring seed pulses with minimal residual cubic chirp after compression.…”
mentioning
confidence: 99%